Interaction of European Carbon Trading and Energy Prices - Derek W. Bunn; Carlo Fezzi (Fondazione Eni Enrico Mattei (FEEM), 2007)
This paper addresses the economic impact of the EU Emission Trading Scheme for carbon on wholesale electricity and gas prices. Specifically, we analyse the mutual relationships between electricity, gas and carbon prices in the daily spot markets in the United Kingdom. Using a structural co-integrated VAR model, we show how the prices of carbon and gas jointly influence the equilibrium price of electricity. Furthermore, we derive the dynamic pass-trough of carbon into electricity price and the response of electricity and carbon prices to shocks in the gas price.
Keywords: Q48; L94; C32; 330; Carbon Emission Trading; Energy Markets; Structural VECM; Klimaschutz; Emissionshandel; Energiemarkt; Fehlerkorrekturmodell; EU-Staaten